Green synthesis of (R)-3-hydroxy-decanoic acid and analogs from levoglucosenone: a novel access to the fatty acid moiety of rhamnolipids - Petracco, Enzo; Flourat, Amandine L.; Belhomme, Marie-Charlotte; Castex, Stéphanie; Brunissen, Fanny; Brunois, Fanny; Peru, Aurélien A. M.; Allais, Florent; Haudrechy, Arnaud (Frontiers in Chemistry, 2024)
Rhamnolipids (RLs) are highly valuable molecules in the cosmetic, pharmaceutic, and agricultural sectors with outstanding biosurfactant properties. In agriculture, due to their potential to artificially stimulate the natural immune system of crops (also known as elicitation), they could represent a critical substitute to conventional pesticides. However, their current synthesis methods are complex and not aligned with green chemistry principles, posing a challenge for their industrial applications. In addition, their bioproduction is cumbersome with reproducibility issues and expensive downstream processing. This work offers a more straightforward and green access to RLs, crucial to decipher their mechanisms of action and design novel potent and eco-friendly elicitors. To achieve this, we propose an efficient seven-step synthetic pathway toward (R)-3-hydroxyfatty acid chains present in RLs, starting from cellulose-derived levoglucosenone, with Michael addition, Baeyer–Villiger oxidation, Bernet–Vasella reaction, and cross-metathesis homologation as key steps. This method allowed the production of (R)-3-hydroxyfatty acid chains and derivatives with an overall yield ranging from 24% to 36%.